Defining Documentation Burden (DocBurden) and Excessive DocBurden for All Health Professionals: A Scoping Review - Levy, Deborah R; Withall, Jennifer B; Mishuris, Rebecca G; Tiase, Victoria; Diamond, Courtney; Douthit, Brian; Grabowska, Monika; Lee, Rachel Y; Moy, Amanda J; Sengstack, Patricia; Adler-Milstein, Julia; Detmer, Don Eugene; et al. (Applied clinical informatics, 2024)
Efforts to reduce documentation burden (DocBurden) for all health professionals (HP) are aligned with national initiatives to improve clinician wellness and patient safety. Yet DocBurden has not been precisely defined, limiting national conversations and rigorous, reproducible, and meaningful measures. Increasing attention to DocBurden motivated this work to establish a standard definition of DocBurden, with the emergence of excessive DocBurden as a term. We conducted a scoping review of DocBurden definitions and descriptions, searching six databases for scholarly, peer-reviewed, and gray literature sources, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extensions for Scoping Review guidance. For the concept clarification phase of work, we used the American Nursing Informatics Association's Six Domains of Burden Framework. A total of 153 articles were included based on a priori criteria. Most articles described a focus on DocBurden, but only 18% ( = 28) provided a definition. We define DocBurden as the stress and unnecessarily heavy work an HP or health care team experiences when usability of documentation systems and documentation activities (i.e., generation, review, analysis, and synthesis of patient data) are not aligned in support of care delivery. A negative connotation was attached to burden without a neutral state in included sources, which does not align with dictionary definitions of burden. Existing literature does not distinguish between a baseline or required task load to conduct patient care resulting from usability issues ( ), and the unnecessarily heavy tasks and requirements that contribute to . Our definition of excessive DocBurden explicitly acknowledges this distinction, to support development of meaningful measures for understanding and intervening on excessive DocBurden locally, nationally, and internationally.